As competências do professor do século XXI: possibilidades de formação em espaços disruptivos de aprendizagem - Santos, Adriana dos (2019)
This work is in line with the Research Processes and Language of the Stricto Sensu Postgraduate Program in Education (PPGEDU) and also with the studies of the Digital Culture Research Group (GEPID), both of the University of Passo Fundo. Currently, it is known that disruptive innovations that modify the contemporary educational scenario, bring with it, questions about new spaces for learning, new teaching methodologies and, especially, new functions for teachers in general. These functions, which require this professional, the development of ski lls and abilities more specific to their work in the context of the twenty-first century, such as the Digital Technological Fluency (FTD), which in turn requires educational professionals to initial teacher training and continued differentiated. In this pe rspective, the problem of this study arises: what are the possibilities of alternative processes of teacher training with a view to the development of digital technological fluency? The general objective of this research is, through the construction of theoretical-pedagogical contributions, together with the accomplishment of an action research, to analyze the issue of teacher training for the context of the 21st century in disruptive learning spaces, with views development of the FTD. For this analysis, the study will be based on the document prepared by the Spanish Government (2017), calling it the Common Frame of Digital Teaching Competence, from which it intends to provide a descriptive reference for the processes of evaluation of training and accreditat ion of digital competence teacher. Emphasis will be placed in this research on the fifth competency described in the above mentioned problem-solving document, but specifically on the fourth sub-competence, referring to the ability of "Innovation and the us e of digital technology in a creative way". This study presents as specific objectives, to understand what is an innovative education, to characterize disruptive learning spaces and their methodological possibilities, to identify the skills and abilities of 21st century teachers and, finally, to analyze the way that disruptive learning spaces, influence teacher training processes for the development of FTD. In order to resolve the central question of this research, it has the theoretical contribution of aut hors such as Bacich (2018), Bonilla (2005), Teixeira (2010), Christensen (2012, 2013, 2015), Delors (2005), Moran (2009, 2012, 2014, 2015), Perrenoud (2000, 2002), Pozo (2002), among other scholars in the area. In this way, research results suggest that disruptive learning spaces can be an efficient alternative for the implementation of teacher training processes for the development and improvement of competencies, especially FTD.